Criminal compliance due diligence in M&A transactions as a criterion to avoid the automatic transfer of criminal liability to the acquiring or resulting legal entity, within the framework of Law No. 30424 - Sota Sánchez, Percy André (2021)
The following paper examines the theoretical foundations of the criminal liability of legal persons in the Peruvian legal system, focusing on the study and criticism of the criminal liability between legal person’s automatic transfer clauses in M&A transactions. It also analyses the relevance of criminal compliance due diligence in M&A transactions and proposes, based on reasonableness criteria, what the components or elements of this due diligence should be.